Continuing Education for Prehospital Healthcare Providers in India – A Novel Course and Concept - Lindquist BD; Koval KW; Acker PC; Bills CB; Khan A; Zachariah S; Newberry JA; Rao GR; Mahadevan SV; Strehlow MC (Open Access Emergency Medicine, 2020)
Benjamin D Lindquist,1 Kathryn W Koval,2 Peter C Acker,1 Corey B Bills,1,3 Ayesha Khan,1 Sybil Zachariah,1 Jennifer A Newberry,1 GV Ramana Rao,4 Swaminatha V Mahadevan,1 Matthew C Strehlow1 1Department of Emergency Medicine, Stanford University School of Medicine, Palo Alto, CA 94304, USA; 2Department of Emergency Medicine, Medical University of South Carolina, Charleston, SC 29425, USA; 3University of California San Francisco, San Francisco, CA 94143, USA; 4GVK Emergency Management and Research Institute, Secunderabad, Telangana 500078, IndiaCorrespondence: Benjamin D Lindquist Email blindqu1@stanford.eduBackground: Emergency medical services (EMS) in India face enormous challenges in providing care to a geographically expansive and diverse patient population. Over the last decade, the public–private-partnership GVK EMRI (Emergency Management and Research Institute) has trained over 100,000 emergency medical technicians (EMTs), with greater than 21,000 currently practicing, to address this critical gap in the healthcare workforce. With the rapid development and expansion of EMS, certain aspects of specialty development have lagged behind, including continuing education requirements. To date, there have been no substantial continuing education EMT skills and training efforts. We report lessons learned during development and implementation of a continuing education course (CEC) for EMTs in India.Methods: From 2014 to 2017, we employed an iterative process to design and launch a novel CEC focused on five core emergency competency areas (medicine and cardiology, obstetrics, trauma, pediatrics, and leadership and communication). Indian EMT instructors and providers partnered in design and content, and instructors were trained to independently deliver the CEC. Many challenges had to be overcome: scale (> 21,000 EMTs), standardization (highly variable skill levels among providers and instructors), culture (educational emphasis on rote memorization rather than practical application), and translation (22 major languages and a few hundred local dialects spoken nationwide).Lessons Learned: During the assessment and development phases, we identified five key strategies for success: (1) use icon-based video instruction to ensure consistent quality and allow voice-over for easy translation; (2) incorporate workbooks during didactic videos and (3) employ low-cost simulation and case discussions to emphasize active learning; (4) focus on non-technical skills; (5) integrate a formal training-of-trainers prior to delivery of materials.Conclusion: These key strategies can be combined with innovation and flexibility to address unique challenges of language, system resources, and cultural differences when developing impactful continuing educational initiatives in bourgeoning prehospital care systems in low- and middle-income countries.Keywords: prehospital care, emergency medical services, prehospital education, continuing medical education